Imaging features and clinical evaluation of pulmonary nodules in children - Dilimulati, Muheremu; Yuan, Shuhua; Jiang, Hejun; Wang, Yahua; Ma, Hui; Shen, Shiyu; Lin, Jilei; Chen, Jiande; Yin, Yong (Frontiers in Oncology, 2024)
Background: With the widespread use of computed tomography (CT), the detection rate of pulmonary nodules in children has gradually increased. Due to the lack of epidemiological evidence and clinical guideline on pulmonary nodule treatment in children, we aimed to provide a reference for clinical diagnosis and management of pediatirc pulmonary nodules. Methods: This retrospective study collected consecutive cases from April 2012 to July 2021 in the Shanghai Children's Medical Center. The sample included children with pulmonary nodules on chest CT scans and met the inclusion criteria. All patients were categorized into tumor and non-tumor groups by pre-CT clinical diagnosis.Nodule characteristics between groups were analyzed. To estabilsh a clinical assessment model for the benign versus malignant pulmonary nodules, patients who have been followed-up for three months were detected and a decision tree model was consturcted and valiadted.The sample comprised 1341 patients with an average age of 7.2±4.6 years.More than half of them (51.7%) were diagnosed with malignancies before CT scan. 48.3% were diagonised with non-tumor diseases or healthy. Compared to non-tumor group, children with tumor were more likely to have multiple nodules in both lungs, larger size and often accompanied by osteolytic or mass lesions. Based on the decision tree model, patients' history of malignancies, nodules diameter size≥5mm, and specific nodule distribution (multiple in both lungs, multiple in the right lung or solitary in the upper or middle right lobe) were important potential predictors for malignity. In the validation set, sensitivity, specificity and AUC were 0.855, 0.833 and 0.828 (95%CI: 0.712-0.909), respectively.This study conducted a clinical assessment model to differentiate benignity and malignancy of pediatric pulmonary nodules.We suggested that a nodule's diameter, distribution and patient's history of malignancies are predictable factors in benign or malignant determination.